Implementation of a spontaneous awakening/ spontaneous breathing trial protocol in a surgical intensive care unit: a before and after study - Desantis, Marianna; Lichtenstern, Christoph; Hagenlocher, Jan-Paul Friedemann; Bruckner, Thomas; Weigand, Markus A.; Kalenka, Armin; Fiedler-Kalenka, Mascha (Minerva Anestesiologica, 2023)
BACKGROUND: Prolonged invasive mechanical ventilation (IMV) influences patient outcome in multiple ways. In this regard the early weaning from IMV is a major goal to be achieved in the treatment of ICU patients. Adopting a weaning protocol that incorporates a Spontaneous Awakening Trial (SAT) and a Spontaneous Breathing Trial (SBT) seems to be essential to reach this goal. Most studies investigating the effectiveness of SAT/SBT protocols in ICU patients' outcomes have focused mainly on medical or mixed (medical and surgical), but not on exclusively surgical patient populations. Surgical patients usually experience more complications and often undergo revision surgeries, therefore needing longer sedation periods and adequate analgo-sedation therapy. Moreover, the longer IMV times make the weaning process more arduous.METHODS: Our retrospective data analysis therefore investigates the effectiveness of a SAT/SBT protocol implementa-tion in the surgical ICU of Heidelberg University Hospital, focusing exclusively on surgical patients and their outcome re-lated to the weaning process. The SAT/SBT protocol was adopted in Heidelberg ICU starting from 05/2019. We therefore analyzed the time period before and after the implementation between 03/2018 and 08/2020. Adult patients who required invasive ventilation for at least 48 hours were screened for study entry. Demographic data, clinical data and SOFA Score on admission, were collected to define the baseline characteristics of the two groups. Only patients with full adherence to the protocol were included. The primary outcome was defined as the successful extubation, intended as an extubation not followed by successive re-intubations until discharge from the ICU. We performed an univariate analysis to evaluate the rate of successful extubations between the two groups.RESULTS: In total, 199 patients were included in the analysis, 98 of which before the SAT/SBT protocol implementa-tion (control group) and 101 after the SAT/SBT protocol implementation (intervention group). The successful extubation rate in the intervention group resulted in 82% (83/101 patients) compared to 64% (63/98 patients) in the control group (P<0.004).CONCLUSIONS: We conclude that even for an exclusively surgical patient population, the implementation of a SAT/ SBT protocol could result in a higher rate of successful extubation.